Characteristics and health care utilization among patients with chronic heart failure: a longitudinal claim database analysis. (26th September 2019) - Wammes, Joost Johan Godert; Auener, Stefan; van der Wees, Philip J.; Tanke, Marit A.C.; Bellersen, Louise; Westert, Gert P.; Atsma, Femke; Jeurissen, Patrick P.T.
Abstract: Aims: This study aimed to determine the characteristics of patients with heart failure and high costs (top 1% and top 2–5% highest costs in perspective of the general population) and to explore the longitudinal health care utilization and persistency of high costs. Methods and results: Longitudinal observational study using claims data from 2006 to 2014 in the Netherlands. We identified all patients that received a hospital treatment for chronic heart failure between 1 January 2008 and 31 December 2010. Of each selected patient, all claims from the Dutch curative health system and with a starting date between 1 January 2006 and 31 December 2014 were extracted. Pharmaceutical and hospital claims were used to establish characteristics and indicators for health care utilization. Descriptive analyses and generalized estimating equation models were used to analyse characteristics, longitudinal health care utilization and to identify factors associated with high costs. Our findings revealed that the difference in costs between top 1%, top 2–5%, and bottom 95% patients with heart failure was mainly driven by hospital costs; and the top 1% group experienced a remarkable increase of mental health costs. Top 1% and top 2–5% patients with heart failure differed from lower cost patients in their higher rate of chronic conditions, excessive polypharmacy, hospital admissions, and heart‐related surgeries. Heart‐related surgeries contributed to the incidental high costs in 54% of top 1% patients, and the costs of the remaining top 1% patients were driven by mental health and pharmaceuticals use and rates of chronic conditions and multimorbidity. Top 1% patients were relatively young. Anaemia, dementia, diseases of arteries, veins and lymphatic vessels, influenza, and kidney failure were significantly associated with high costs. The end‐of‐life period was predictive of top 1% and top 5% costs. More than 90% of the population incurred at least one top 5% year during follow‐up, and 31.8% incurred at least one top 1% year. Fifty‐seven per cent incurred multiple top 5% years whereas only 8.6% incurred multiple top 1% years. Top 5% years were more frequently consecutive than top 1% years. Conclusions: Top 1% utilization occurs predominantly incidentally and among less than a third of patients with heart failure, whereas almost all patients with heart failure experience at least one top 5% year, and more than half experience two or more top 5% years. Both medical and psychiatric/psychosocial needs contribute to high costs in heart failure patients. Comprehensive and integrated efforts are needed to further improve quality of care and reduce unnecessary costs.